Psoriasis: classical and emerging comorbidities - Maria de Fátima Santos Paim de Oliveira; Bruno de Oliveira Rocha; Gleison Vieira Duarte (Sociedade Brasileira de Dermatologia, 2015)
Psoriasis is a chronic inflammatory systemic disease. Evidence shows an association of psoriasis with arthritis, depression, inflammatory bowel disease and cardiovascular diseases. Recently, several other comorbid conditions have been proposed as related to the chronic inflammatory status of psoriasis. The understanding of these conditions and their treatments will certainly lead to better management of the disease. The present article aims to synthesize the knowledge in the literature about the classical and emerging comorbidities related to psoriasis.